Current Issues in Global Health - Claborn, David (IntechOpen, 2018)
Current Issues in Global Health provides a forum for a broad discussion of health issues, from systemic violence to infectious disease in places as far apart as Kashmir and South America. The authors come from a variety of environments including military and academic positions. Despite the diversity of subject matter and authors, the consistent theme of the book always focuses on the provision of an environment in which members of a community can achieve or maintain good public health. The subjects addressed here are those that cross international borders and affect lives around the world, thus truly qualifying as issues of global health importance.